Perceptions of Others in Self-Descriptions of Children and Adolescents in India - Kuebli, Janet and Reddy, Ranjini and Gibbons, Judith L. (Cross-Cultural Research, 1998)
Participants in this study were 190 children in three age groups (ages 9-11, 12-14, and 15-16) from three school groups of different socioeconomic status (SES) (low, middle, high) who wrote responses to the question, "How would you describe yourself to yourself?" Content analyses were conducted to identify references to others in children's self-descriptions. Both function and person identity of references to others were coded. References to others were most frequent for children from low SES, and mention of others overall became more generic and depersonalized with increasing age. Girls mentioned qualities of their relationships with others more than boys did. Results indicate that self-construals vary considerably within culture as well as by social class, age, and gender.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMDY5Mzk3MTk4MDMyMDAzMDI